Leptobasis linda sp. nov. from Ecuador (Odonata: Coenagrionidae) - Johnson, Jim T. (Zootaxa, 2016)
Leptobasis linda is described from the Pacific lowlands of Ecuador. The coloration of mature individuals is superficially similar to the widespread L. vacillans, but structural and color characteristics differentiate L. linda from all congeneric species. The male caudal appendages and the female posterior margin of the prothorax are unique among Leptobasis.